2016
DOI: 10.1038/ncomms11293
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of lysenin pore elucidates membrane insertion by an aerolysin family protein

Abstract: Lysenin from the coelomic fluid of the earthworm Eisenia fetida belongs to the aerolysin family of small β-pore-forming toxins (β-PFTs), some members of which are pathogenic to humans and animals. Despite efforts, a high-resolution structure of a channel for this family of proteins has been elusive and therefore the mechanism of activation and membrane insertion remains unclear. Here we determine the pore structure of lysenin by single particle cryo-EM, to 3.1 Å resolution. The nonameric assembly reveals a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
163
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(182 citation statements)
references
References 47 publications
8
163
0
1
Order By: Relevance
“…4b) [86]. The cryo-EM structures of a number of pore-forming toxins that assemble into large pores to disturb essential cellular gradients, usually featuring > 10 subunits, were also determined, giving important insights into conformational changes during membrane insertion [87, 88]. Cryo-EM studies on Tc toxin complexes from Photorhabdus luminescens revealed a unique syringe-like injection and translocation mechanism for membrane permeation and delivery of the toxic component into host cells (Fig.…”
Section: Single-particle Cryo-em Of Biomedically Relevant Proteinsmentioning
confidence: 99%
“…4b) [86]. The cryo-EM structures of a number of pore-forming toxins that assemble into large pores to disturb essential cellular gradients, usually featuring > 10 subunits, were also determined, giving important insights into conformational changes during membrane insertion [87, 88]. Cryo-EM studies on Tc toxin complexes from Photorhabdus luminescens revealed a unique syringe-like injection and translocation mechanism for membrane permeation and delivery of the toxic component into host cells (Fig.…”
Section: Single-particle Cryo-em Of Biomedically Relevant Proteinsmentioning
confidence: 99%
“…Lysenin is a component of the earthworm's immune system, exerting its function by attacking membranes of parasites . In addition to the X‐ray structure of the lysenin monomer, the 3.1 Å structures of the pore, determined independently using cryo‐EM and X‐ray crystallography, have helped to identify the functional folds and interactions of the three separate domains of the lysenin monomer [Fig. (A,B)].…”
Section: Members Of β‐Pore Forming Proteinsmentioning
confidence: 99%
“…In contrast, the cap‐domain exhibits a moderate structural deformation while the PFM undergoes a major conformational alteration, with some residues moving as far as 100 Å, during prepore‐to‐pore formation. The crystal structure of lysenin in complex with sphingomyelin combined with a bending deformation of the cap domain further suggests that structural changes triggered in the cap domain might include the molecular sensor that initiates the prepore‐to‐pore transition. These structural data have been instrumental in designing experiments to better understand lysenin pore formation versus substrate interaction events .…”
Section: Members Of β‐Pore Forming Proteinsmentioning
confidence: 99%
See 2 more Smart Citations